Passive acoustic monitoring data recorded by recorder SV1014 at mooring AWI245-5 in the Weddell Sea, Southern Ocean, in 2019/2020 - Karolin Thomisch; Stefanie Spiesecke; Diego Filun; Marlene Meister; Clea Parcerisas; Irene Roca; Sarah Zwicker; Olaf Boebel (PANGAEA, 2024)
Passive acoustic monitoring (PAM) data were collected by recorder SV1014 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 69.0607° S, 17.3913° W, mooring AWI245-5, in the Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from January 2019 to April 2022, passive acoustic data were collected from January 2019 to July 2020 (recording period) by SV1014 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 300 m depth and scheduled to record continuously at a sample rate of 24,000 Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 1+, according to the standards defined in the associated Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).